2012
DOI: 10.1098/rstb.2011.0229
|View full text |Cite
|
Sign up to set email alerts
|

Development of real-time radioisotope imaging systems for plant nutrient uptake studies

Abstract: Ionic nutrition is essential for plant development. Many techniques have been developed to image and (or) measure ionic movement in plants. Nevertheless, most of them are destructive and limit the analysis. Here, we present the development of radioisotope imaging techniques that overcome such restrictions and allow for real-time imaging of ionic movement. The first system, called macroimaging, was developed to visualize and measure ion uptake and translocation between organs at a whole-plant scale. Such a devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 18 publications
1
40
0
Order By: Relevance
“…Consistent with PHT1 transporters being induced by Pi starvation (Misson et al, 2005;Kanno et al, 2012), a higher Pi influx capacity was observed in Pi-starved seedlings (compare -Pi with +Pi in Fig. 2B).…”
Section: Ptn Alters the Pi Transporter Regulations Triggered By Pi Stsupporting
confidence: 78%
“…Consistent with PHT1 transporters being induced by Pi starvation (Misson et al, 2005;Kanno et al, 2012), a higher Pi influx capacity was observed in Pi-starved seedlings (compare -Pi with +Pi in Fig. 2B).…”
Section: Ptn Alters the Pi Transporter Regulations Triggered By Pi Stsupporting
confidence: 78%
“…These cluster roots are formed as part of the normal root developmental programme rather than as a responsive change [105], and are an example of a root structure which appears to have evolved primarily for the maximization of phosphorus acquisition from the soil [106,107]. In this issue, Nussaume et al [108] discuss a novel imaging technique for the visualization of nutrient uptake.…”
Section: Control Of Root Branching In Arabidopsis (A) Hormonesmentioning
confidence: 99%
“…HPLC (Uwimana et al 2012). A more sophisticated technique was the imaging of ionic movements in plants using real-time radioisotope imaging systems (in this case 32 P) by Kanno et al 2012, which however appears to be too complex for efficient screening. Recently, a system using NMR or positron emission tomography provided very useful information, but would be even more difficult to apply in practice (De Smet et al 2012).…”
Section: Hydroponics: Growing Plants On Water Solutionsmentioning
confidence: 99%